Catalytic gasification of oil palm frond biomass in supercritical water for hydrogen production using supported and doped magnesium oxide catalysts - Mastuli, Mohd Sufri (2019)
Utilization of hydrogen as an energy carrier for transportation sector and other energy utilities could reduce the dependency on conventional fossil fuels and cater the increasing energy demands. The combustion of hydrogen gas (H2) in a fuel cell engine produces only water as its by-product with zero greenhouse gases that did not promoting the global warming. Production of H2 from biomass is one of the ultimate goals in renewable and sustainable energy development program. Various technologies have been developed for the conversion of biomass into combustible hydrogen. In this study, supercritical water gasification (SCWG) was used to convert the oil palm frond (OPF) biomass into H2-rich syngas. Two series of catalysts namely supported and doped magnesium oxide (MgO) catalysts were synthesized and characterized before catalyzing the SCWG reaction that enhanced the total H2 yield. Non-noble metal supported catalysts such as 20NiO/MgO, 20CuO/MgO and 20ZnO/MgO were synthesized using an impregnation method. The 20ZnO/MgO catalyst found to be produced the highest H2 yield even though it possessed the smallest specific surface area. Other factors such distribution, basicity and bond strength of the catalysts played important roles for higher catalytic performances. It is also believed that the catalyst stability can be further improved by doping the active metal into the crystal structure of the MgO catalyst. Therefore, the Ni doped MgO catalysts (Mg1-xNixO) and the Zn doped MgO catalysts (Mg1-xZnxO) with x = 0.05, 0.10, 0.15, 0.20, were synthesized using a self-propagation combustion method. Interestingly, the Rietveld refinements showed contraction of crystal structure for the Ni doped MgO catalysts and expansion of crystal structure for the Zn doped MgO catalysts, upon increasing the metal contents. It means the crystallite size, surface area, porosity and basicity were affected. The correlation between catalytic performance and properties for selected supported and doped MgO catalysts were investigated. The doped catalysts have larger surface areas than the supported catalysts, which can be arranged in the order of Mg0.80Ni0.20O (67.9 m2 g-1) > Mg0.80Zn0.20O (36.3 m2 g-1) > 20NiO/MgO (30.1 m2 g-1) > 20ZnO/MgO (13.1 m2 g-1). Whether supported or doped, the Ni-based catalysts always exhibited larger surface area than that of the Zn-based catalysts. Unexpectedly, the Zn-based catalysts produced higher H2 yield from the SCWG of OPF biomass although these catalysts have smaller surface areas. When compared to the non-catalytic SCWG reaction, the H2 yield increased by 187.2% for 20NiO/MgO, 269.0% for 20ZnO/MgO, 361.7% for Mg0.80Ni0.20O, and 438.1% for Mg0.80Zn0.20O. The Mg0.80Ni0.20O catalyst gave the highest H2 yield because it had the highest number of basic sites approximately twenty-fold higher than that of the 20ZnO/MgO catalyst. It also proved to be the most stable catalyst, as verified from the X-Ray photoelectron spectroscopy (XPS) outcomes. As such, this study concludes that the catalytic performances do not only depend on the specific surface area, but also influenced by the basicity properties and the catalyst stability. In addition, the doped catalysts may serve as a new catalyst system for the SCWG for hydrogen production.